1999
DOI: 10.1002/srin.199905659
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the solidification structure of continuously cast slabs

Abstract: A study of solidification phenomena performed under industrial conditions is presented. The solidification structure of high carbon, medium carbon and microalloyed steel grades was observed and correlated to casting parameters such as superheat and secondary cooling. Experimental data of dendrite morphology are related to calculated solidification variables. The calculation is based on the solution of the enthalpy balance equation. An expression for the dependence of secondary dendrite arm spacing on solidific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
0
22
0
3
Order By: Relevance
“…Several correlations and measurements of SDAS are reported in literature. 27,28) Won and Thomas 22) have critically analyzed some of them and proposed the following correlations. The investigators 22) have demonstrated the applicability of their correlations over a wide range of carbon concentration.…”
Section: Estimation Of Secondary Dendrite Arm Spacing For Various Carmentioning
confidence: 99%
“…Several correlations and measurements of SDAS are reported in literature. 27,28) Won and Thomas 22) have critically analyzed some of them and proposed the following correlations. The investigators 22) have demonstrated the applicability of their correlations over a wide range of carbon concentration.…”
Section: Estimation Of Secondary Dendrite Arm Spacing For Various Carmentioning
confidence: 99%
“…Using SDAS valto approximate the dendrites. Battle and Pehlke [36] developed ues measured by several different researchers [47][48][49][50][51] at various a similar numerical model for plate dendrites and included cooling rates and steel carbon contents, an empirical relationcoarsening of the dendrite arms. The approach of Matsumiya ship was obtained by a best fit as follows: et al has been developed further to consider the ␦/␥ transformation, which occurs during solidification of steels.…”
Section: Previous Workmentioning
confidence: 99%
“…For carbon contents lower than 0.53 wt pct, when the melt cools down slightly below the liquidus temperature, solid nucleates and grows as ␦ phase until solidification is complete (low carbon content) or until the peritectic temperature is reached (middle carbon content). At the peritectic temperature, solid ␥ phase starts to form around the periphery of spacings [47][48][49][50][51] as a function of carbon content at various cooling rates.…”
Section: Peritectic Phase-transformation Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research studies have been carried out with the aim of understanding the SDAS in steels. According to theoretical investigations from the past, the following relationships between SDAS (l 2 ) and solidification parameters have been established [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The symbols and definitions are listed in Table 1. Material constants a n and exponents b n depend on steel composition.…”
Section: Introductionmentioning
confidence: 99%